2020
DOI: 10.1002/slct.202004130
|View full text |Cite
|
Sign up to set email alerts
|

Construction of the Copper‐Functionalized Covalent Organic Framework Used as a Heterogeneous Catalyst for Click Reaction

Abstract: Functional modification of the covalent organic frameworks (COFs) has become an efficient strategy to expand its applications in various fields. In this investigation, an imine linked T−D COF has been synthesized via solvothermal method using 2,4,6‐tris(4‐aminophenyl)pyridine (TAPP) and 2,6‐dihydroxynaphthalene‐1,5‐dicarbaldehyde (DHNDA) as building blocks. While synthesizing T‐D COF, hydroxyl groups are strategically introduced to the adjacent sites of −C=N− bonds in the framework. Such a special structure en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…2.82° for TAPT‐DHNDA assigned to the (100) reflection plane can be observed in the PXRD pattern, which substantiates its ordered crystalline structures. Moreover, the experimental PXRD pattern of TAPT‐DHNDA is in good consistence with the simulated patterns calculated from AA stacking model (Figure 4 c, S14 and Table S2) and the previous report [32] . Crystalline TAPT‐DHNDA membrane demonstrates the morphology of randomly well‐intergrown grains (Figure 4 e).…”
Section: Resultssupporting
confidence: 86%
“…2.82° for TAPT‐DHNDA assigned to the (100) reflection plane can be observed in the PXRD pattern, which substantiates its ordered crystalline structures. Moreover, the experimental PXRD pattern of TAPT‐DHNDA is in good consistence with the simulated patterns calculated from AA stacking model (Figure 4 c, S14 and Table S2) and the previous report [32] . Crystalline TAPT‐DHNDA membrane demonstrates the morphology of randomly well‐intergrown grains (Figure 4 e).…”
Section: Resultssupporting
confidence: 86%
“…In 2020, Gao and co-workers reported the Cu@T-D COF by metalating the ( E )-1-((phenylimino)methyl)naphthalen-2-ol moiety in the T-D COF. 293 Since the T-D COF contains pyridyl donors, the definite location of Cu( ii ) deserves further study.…”
Section: Synthetic Strategy Of Metalated Cofsmentioning
confidence: 99%
“…In 2020, Gao et al demonstrated that the click reaction of terminal alkynes with azides can be achieved by a Cu( ii )-functionalized COF with sodium ascorbate as the reducing agent. 293 For the reaction of phenylacetylene with benzyl azide at 60 °C, the yields in methanol, ethanol, acetonitrile, and water are all above 80%, and the reaction proceeds almost quantitatively in a mixed solvent system of methanol and water. However, the reducing agent used in this reaction cannot be recovered, which increases the cost of the reaction.…”
Section: Application Of Metalated Cofsmentioning
confidence: 99%
“…2.828 8 for TAPT-DHNDAassigned to the (100) reflection plane can be observed in the PXRD pattern, which substantiates its ordered crystalline structures.M oreover, the experimental PXRD pattern of TAPT-DHNDAisin good consistence with the simulated patterns calculated from AA stacking model (Figure 4c,S 14 and Table S2) and the previous report. [32] Crystalline TAPT-DHNDAm embrane demonstrates the morphology of randomly well-intergrown grains (Figure 4e). TGA curve (Figure S15) reveals that TAPT-DHNDAm embrane is stable up to ca.…”
Section: Forschungsartikelmentioning
confidence: 99%